2016
DOI: 10.14423/smj.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends in the Prevalence of Diabetes Mellitus in an Urban Emergency Department

Abstract: Objective The objective of this study was to examine the longitudinal trends in diabetes mellitus (DM) in emergency department (ED) patients and evaluate the factors associated with those trends. Methods We conducted a retrospective analysis of all patients who presented to the ED from 2006 to 2011. The presence of DM, height, and weight were recorded prospectively. The study was conducted in the ED of an urban, academic hospital with an average yearly volume of approximately 62,000 patients. Inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The objective of this study was to investigate the age distribution of patients with type 2 diabetes in light of American Diabetes Association screening recommendations at age 45. Previous studies showed that claims data can be used to estimate the prevalence of diabetes and its associated complications and that claims data compare favorably with traditional health survey estimates (2,13). These studies demonstrated that the demographic distribution of unique emergency patients is similar to the demographic distribution of census estimates of the general population and is thus useful for tracking diabetes cross-sectionally for a large proportion of the population in a given geographic area (2).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to investigate the age distribution of patients with type 2 diabetes in light of American Diabetes Association screening recommendations at age 45. Previous studies showed that claims data can be used to estimate the prevalence of diabetes and its associated complications and that claims data compare favorably with traditional health survey estimates (2,13). These studies demonstrated that the demographic distribution of unique emergency patients is similar to the demographic distribution of census estimates of the general population and is thus useful for tracking diabetes cross-sectionally for a large proportion of the population in a given geographic area (2).…”
Section: Introductionmentioning
confidence: 99%
“…B ecause the prevalence of diabetes mellitus or chronic renal failure on hemodialysis is increasing, 1,2) the incidence of complex calcified lesions is also increasing in the current percutaneous coronary interventions (PCI). 3) Rotational atherectomy (RA) is mostly used for lesion modifications in severely calcified lesions in the current PCI.…”
mentioning
confidence: 99%
“…There are various studies in the international literature, regarding dietary standards related to clinical indicators of diabe-tes [4] with prevalence of obesity [5,6], but also of the classical risk factors, such as predisposition [7], cardiovascular diseases [8], dyslipidemia [9,10], high blood pressure (hypertension) [11]. And age [12] in diabetic population.…”
Section: Introductionmentioning
confidence: 99%